Assessment of Early Fuchs Endothelial Corneal Dystrophy and CTG Trinucleotide Expansion Positivity Using Scheimpflug Imaging - Stanley S.J. Poh, MBBS; Kai Yuan Tey, MBBS; Gary S.L. Peh, PhD; Dawn J.H. Neo, MSc; Hla Myint Htoon, PhD; Evan K.L. Lee; Yu Qiang Soh, MBBS; V Vinod Mootha, MD; Jodhbir S. Mehta, PhD (Ophthalmology Science)
Purpose: To evaluate changes in corneal densitometry and optical aberrations using Scheimpflug imaging in early Fuchs endothelial corneal dystrophy (FECD) and to assess their association with CTG trinucleotide repeat expansion. Design: Retrospective cross-sectional study. Subjects: Fuchs endothelial corneal dystrophy eyes diagnosed between 2018 and 2022 were included. Control eyes were recruited from healthy individuals undergoing cataract surgery. Methods: All eyes underwent Scheimpflug imaging. Subclinical edema was defined by the presence of ≥2 of the following features: (1) loss of parallel isopachs; (2) displacement of the thinnest point; and (3) focal posterior depression. A subset of FECD subjects was genotyped for CTG repeat expansion. Main Outcome Measures: Corneal densitometry, higher-order aberration (HOA), and pachymetry were quantified. Densitometry was measured across 3 layers (anterior 120 μm, central, and posterior 60 μm) and within 4 concentric annuli while HOA was analyzed separately for the anterior and posterior cornea. Results: One hundred eight FECD cases and 59 controls were included. Eyes with subclinical edema exhibited significantly higher densitometry and HOA across all corneal layers and zones compared with those without edema (all P < 0.01). Subclinical edema was independently associated with increased posterior corneal HOA (β = 15.068, 95% confidence interval [CI]: 7.546–22.590) and elevated densitometry in the central 0 to 2 mm annulus across all layers. Among genotyped eyes, 22 (44.0%) were positive for CTG expansion, which was associated with lower densitometry in the anterior (β = −4.59, 95% CI: −7.28 to −1.92), central (β = −1.76, 95% CI: −2.79 to −0.74), and posterior (β = −3.05, 95% CI: −5.67 to −0.44) layers of the central 0 to 2 mm annulus. Conclusions: Fuchs endothelial corneal dystrophy eyes with subclinical edema are associated with increased corneal densitometry and HOA, indicating early structural and optical changes. In contrast, the presence of CTG repeat expansion was correlated with reduced central corneal densitometry, suggesting a potentially distinct disease phenotype. Financial Disclosure(s): Proprietary or commercial disclosure may be found in the Footnotes and Disclosures at the end of this article.